TODAY, MEASURES TO PREVENT HEPATITIS D DISEASE - Esonova Orzigul Shamshiddinovna (Galaxy International Interdisciplinary Research Journal, 2024)
Hepatitis D, also known as Hepatitis Delta, is a serious liver infection caused by the Hepatitis D virus (HDV). It is a satellite virus that requires the presence of Hepatitis B virus (HBV) to replicate. Prevention of Hepatitis D is closely tied to controlling Hepatitis B infection through vaccination, public health education, and targeted prevention strategies. This article explores key preventive measures against Hepatitis D, reviewing the latest literature, methodologies for prevention, and the significance of vaccination in controlling this disease.